2021
DOI: 10.31801/cfsuasmas.810424
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability characteristics of the standard two-sided power distribution

Abstract: In this study, the standard two-sided power (STSP) distribution is considered with regard to statistical reliability analysis in detail. For this purpose, along with the reliability and hazard functions of the distribution, particular reliability indices that are useful in maintenance and replacement policies are obtained and they are evaluated with their plots. The STSP distribution is classified based on aging according to various cases of its parameters. Then, we studied the classical and Bayesian estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The squared error loss function (SELF) is the most commonly used loss function because it is symmetrical and it provides equal distance to the losses through overestimation and underestimation. The performances of the Bayes estimations under the different loss functions are handled by [6] and it is observed that there are no significant differences between them. Therefore, we propose to use SELF as a symmetrical loss function.…”
Section: Bayes Estimation Of R Skmentioning
confidence: 99%
“…The squared error loss function (SELF) is the most commonly used loss function because it is symmetrical and it provides equal distance to the losses through overestimation and underestimation. The performances of the Bayes estimations under the different loss functions are handled by [6] and it is observed that there are no significant differences between them. Therefore, we propose to use SELF as a symmetrical loss function.…”
Section: Bayes Estimation Of R Skmentioning
confidence: 99%